Thermally conductive composition

JP7933460B2Active Publication Date: 2026-10-13SHIN ETSU CHEMICAL CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2024576280
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-02-09
Filing Date
2024-02-01
Publication Date
2026-10-13
Estimated Expiration
2044-02-01

AI Technical Summary

Benefits of technology

【0010】 本発明の熱伝導性組成物は、界面活性が強く、押し広げた際に十分にぬれ広がり、作業性に優れ、さらに高い熱伝導率を有する。したがって、本発明の組成物は、従来のガリウム又はガリウム合金単独では表面張力により液滴状になり取り扱いが困難であった部材に対して有用である。また、(B)成分の平均粒子径が異なるものを組み合わせることで、70W/m·K以上の高い熱伝導率を有し、作業性にも優れる熱伝導性組成物を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007933460000007
    Figure 0007933460000007
  • Figure 0007933460000008
    Figure 0007933460000008
  • Figure 0007933460000001
    Figure 0007933460000001
Patent Text Reader

Abstract

Provided is a thermally conductive composition having excellent thermal conductivity and excellent workability. This thermally conductive composition has: 100 parts by mass of (A) gallium and / or an alloy thereof having a melting point in the range of -20°C to 100°C; and, with respect to 100 parts by mass of the (A) component, 2-150 parts by mass of (B) a metal oxide and / or a metal nitride having an average particle diameter of 0.01-200 µm. The total content rate of the (A) component and the (B) component in the composition is 95-100 mass%. In the thermally conductive composition, a gallium alloy of the (A) component is at least one selected from Ga-In alloys, Ga-Sn-Zn alloys, Ga-In-Sn alloys, and Ga-In-Bi-Sn alloys.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a thermally conductive composition that has excellent thermal conductivity and workability. [Background technology]

[0002] Many heat-generating electronic components mounted on printed circuit boards, such as CPUs, widely utilize heat sinks and other heat dissipation devices to prevent damage and performance degradation due to temperature increases during use. Generally, thermally conductive materials are used between the heat-generating electronic component and the heat dissipation device to efficiently transfer the heat generated by the component. However, with the increasing performance of electronic components, the amount of heat generated tends to increase, creating a demand for the development of materials and components with even greater thermal conductivity than conventional ones.

[0003] Generally, electrical and electronic components generate heat during use, so heat dissipation measures are necessary to ensure proper operation of these components, and various thermally conductive materials have been proposed for this purpose. These thermally conductive materials can be broadly classified into two forms: 1) easy-to-handle sheet-like materials, and 2) paste-like materials. While heat dissipation sheets can be easily mounted on heat-generating electronic components and heat sinks, the resulting gaps at the interface with the components and heat sinks increase interfacial thermal resistance, leading to insufficient heat conduction. On the other hand, paste-like heat dissipation materials, due to their liquid-like properties, have less impact on the surface irregularities of heat-generating electronic components and heat sinks, allowing them to adhere closely to both and reduce interfacial thermal resistance, but they do not provide sufficient heat dissipation performance.

[0004] For example, Patent Documents 1 to 5 propose silicone resins into which low-melting-point metals or metal fillers are incorporated as components to impart thermal conductivity. However, even with these advancements, the increasing heat generation due to the high integration and high speed of heat-generating electronic components in recent years has resulted in insufficient thermal conductivity from these thermally conductive materials. Furthermore, in conventional thermally conductive compositions, the inclusion of base oils used as substrates, such as polyorganosiloxanes (including silicone oils, silicone rubbers, and silicone resins) or hydrocarbon-based synthetic oils, can reduce the thermal conductivity of the thermally conductive composition. Therefore, it is desirable to exclude these materials.

[0005] Patent documents 6 to 8 disclose heat dissipation greases that use a low-melting-point metal (including alloys of gallium, indium, and tin) as a base material and contain a thermally conductive filler. The types of fillers disclosed are tungsten, molybdenum, and metallic silicon in Patent Document 7, boron nitride, alumina, and aluminum nitride in Patent Document 6, and ceramic powder in Patent Document 8. However, Patent Documents 6 and 8 do not evaluate the appearance, workability, thermal conductivity, etc., of the compositions. Regarding Patent Document 9, the filler is a metal fine powder, and in the examples, silver powder or copper powder is used, but the thermal conductivity is about 10-30 W / (m·K), which is not sufficient. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] Japanese Patent Publication No. 2003-176414 [Patent Document 2] Japanese Patent Publication No. 2005-112961 [Patent Document 3] Japanese Patent Publication No. 2003-218296 [Patent Document 4] Japanese Patent Publication No. 2004-039829 [Patent Document 5] Japanese Patent Publication No. 2007-106809 [Patent Document 6] Japanese Patent Application Publication No. 03-071992 [Patent Document 7] Japanese Patent Publication No. 2001-329068 [Patent Document 8] Japanese Patent Publication No. 2004-071816 [Patent Document 9] Japanese Patent Publication No. 2012-111823 [Overview of the project] [Problems that the invention aims to solve]

[0007] Therefore, the object of the present invention is to provide a thermally conductive composition that is substantially free of base oils used as substrates in conventional thermally conductive compositions, such as polyorganosiloxanes (including silicone oils, silicone rubbers, and silicone resins) and hydrocarbon-based synthetic oils, and that exhibits excellent thermal conductivity and workability. [Means for solving the problem]

[0008] As a result of diligent research to solve the above problems, the inventors have developed a thermally conductive composition that reduces the fluidity of low-melting-point metals, improves workability in a paste-like form, and has a high thermal conductivity of 30 W / m·K or higher, by blending gallium and / or gallium alloys with metal oxides and / or metal nitrides of a specific particle size. The thermal conductive composition can be placed between a heat-generating electronic component and a heat dissipation member, similar to conventional thermal conductive greases, and by conforming to the surface irregularities of the component or member without creating gaps, it can be used as a thermal conductive layer with low thermal resistance. The heat generated when the heat-generating electronic component is operating is quickly conducted to the heat dissipation member via the thermal conductive layer containing gallium and / or its alloy, which is maintained in the structure described above, resulting in excellent heat dissipation performance. Based on this finding, the present invention was completed. In other words, the present invention provides the following thermally conductive composition.

[0009] [1] (A) Gallium and / or its alloys having a melting point of -20 to 100°C: 100 parts by mass, (B) Metal oxides and / or metal nitrides with an average particle size of 0.01 μm to 200 μm: 2 to 150 parts by mass per 100 parts by mass of component (A) A thermally conductive composition containing the above-mentioned (A) and (B), wherein the total content of the above-mentioned (A) and (B) in the composition is 95 to 100% by mass. [2] The thermally conductive composition according to [1], wherein the total content of component (A) and component (B) in the composition is 98 to 100% by mass. [3] The thermally conductive composition according to [1] or [2], wherein the gallium alloy of component (A) is one or more selected from Ga-In alloy, Ga-Sn-Zn alloy, Ga-In-Sn alloy, and Ga-In-Bi-Sn alloy. [4] A thermally conductive composition according to any one of the following [1] to [3], wherein component (B) is one or more selected from zinc oxide powder, alumina powder, boron nitride powder, silicon nitride powder, aluminum nitride powder, aluminum hydroxide powder, and magnesium oxide powder. [5] Furthermore, the thermally conductive composition according to any one of the following [1] to [4], comprising 0.01 to 10 parts by mass of the following hydrophobic spherical silica fine particles as component (C) per 100 parts by mass of component (A). On the surface of hydrophilic spherical silica nanoparticles consisting substantially of SiO2 units, obtained by hydrolysis and condensation of a tetrafunctional silane compound, its partially hydrolyzed condensation product, or a mixture thereof, R 1 SiO 3 / 2 Unit (R 1 (is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms), and R 2 3SiO 1 / 2 Unit (each R) 2 These are monovalent hydrocarbon groups (which are identical or different, substituted or unsubstituted, with 1 to 8 carbon atoms) that have been introduced, with a particle size in the range of 0.005 to 1 μm and a particle size distribution D 90 / D 10 Hydrophobic spherical silica nanoparticles having a value of 3 or less and an average circularity of 0.8 to 1. [6] Furthermore, the thermally conductive composition according to any one of [1] to [5], which contains, as component (D), an organosilane represented by the following general formula (1) in an amount of 0.001 to 10 parts by mass relative to 100 parts by mass of component (A). R 1 a R 2 b Si(OR 3 ) 4-a-b (1) (wherein each R 1 is independently a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, each R 2 is independently a substituted or unsubstituted monovalent hydrocarbon group other than an alkyl group, R 3 are the same or different monovalent hydrocarbon groups having 1 to 6 carbon atoms, a is a number of 1 to 3, b is a number of 0 to 2, and the sum of a and b is a number of 1 to 3.) [Effects of the Invention]

[0010] The thermally conductive composition of the present invention has high surface activity, sufficiently spreads and wets when spread, exhibits excellent workability, and further has high thermal conductivity. Therefore, the composition of the present invention is useful for members that were difficult to handle with conventional gallium or gallium alloy alone, which would form droplets due to surface tension. Furthermore, by combining components (B) having different average particle diameters, a thermally conductive composition having a high thermal conductivity of 70 W / m·K or more and excellent workability can be obtained. [Brief Description of the Drawings]

[0011] [Figure 1] A photograph showing that when the discharged composition is spread with a spatula, it is in a state of sufficiently spreading and wetting. [Figure 2] A photograph showing that when the discharged composition is spread with a spatula, it is in a state of not sufficiently spreading and wetting. [Mode for Carrying Out the Invention]

[0012] Hereinafter, the present invention will be described in detail.

[0013] (A) component Component (A) of the composition of the present invention is gallium and gallium alloy, and its melting point must be in the range of -20 to 100°C. Components with a melting point below -20°C are difficult to manufacture and therefore uneconomically undesirable. Components with a melting point above 100°C do not melt quickly during the composition preparation process, resulting in poor workability or precipitation and non-uniformity during manufacturing. Therefore, gallium or gallium alloy with a melting point in the range of -20 to 100°C is an economically and practically necessary and appropriate condition for handling. Components with a melting point in the range of -20 to 50°C are particularly preferred.

[0014] The melting point of metallic gallium is 29.8°C. Representative gallium alloys with melting points within this range include, for example, gallium-indium alloys (e.g., Ga-In, mass ratio = 75.4:24.6, melting point = 15.7°C), gallium-tin alloys, gallium-tin-zinc alloys (e.g., Ga-Sn-Zn, mass ratio = 82:12:6, melting point = 17°C), and gallium-indium-tin alloys (e.g., Ga-In- Examples include Sn (mass ratio = 68.5:21.5:10, melting point = 19°C; mass ratio = 62.0:25.0:13.0, melting point = 5.0°C; mass ratio = 21.5:16.0:62.5, melting point = 10.7°C), and gallium-indium-bismuth-tin alloys; for example, Ga-In-Bi-Sn (mass ratio = 9.4:47.3:24.7:18.6, melting point = 48.0°C).

[0015] (A) Component can be used alone or in combination of two or more components.

[0016] The gallium and / or alloy present in the composition of the present invention is a low-melting-point metal and is used as a base material. In other words, the low-melting-point metal is the main component of the thermally conductive composition of the present invention. Furthermore, if base oils used as substrates in conventional thermally conductive compositions, such as polyorganosiloxanes (including silicone oils, silicone rubbers, and silicone resins) or hydrocarbon-based synthetic oils, are incorporated into the composition of the present invention, the thermal conductivity of the composition of the present invention may decrease. Therefore, it is preferable not to include these, and the upper limit of their content in the overall composition of the present invention is preferably 1.0% by mass or less, more preferably 0.5% by mass or less, and particularly preferably substantially absent.

[0017] (B) Component The composition of the present invention contains a metal oxide and / or metal nitride as a thermally conductive filler. The type of thermally conductive filler is not particularly limited, and powders conventionally used in heat dissipation (thermally conductive) greases can be used. In particular, those with high thermal conductivity are preferred, and one or more selected from zinc oxide powder, alumina powder, boron nitride powder, silicon nitride powder, aluminum nitride powder, aluminum hydroxide powder, and magnesium oxide powder are preferred. These thermally conductive fillers may be used after their surface has been hydrophobized with organosilane, organosilazane, organopolysiloxane, organofluorine compounds, etc., as needed.

[0018] The average particle size of the thermal conductive filler is 0.01 to 200 μm, preferably 0.1 to 150 μm, and more preferably 0.5 to 120 μm. If the average particle size of the thermal conductive filler is less than 0.01 μm or more than 200 μm, it may be undesirable because the packing rate in the resulting composition cannot be increased. These thermal conductive fillers may be used individually or as a mixture of two or more types with different average particle sizes. The above average particle size is the cumulative average diameter based on volume. The average particle size can be measured using a laser diffraction / scattering particle size distribution analyzer, for example, using the Microtrac MT3300EX particle size analyzer manufactured by Nikkiso Co., Ltd.

[0019] The amount of thermally conductive filler added is in the range of 2 to 150 parts by mass per 100 parts by mass of component (A), preferably in the range of 2 to 100 parts by mass, more preferably in the range of 2 to 80 parts by mass, and even more preferably in the range of 5 to 60 parts by mass. If the amount of thermally conductive filler added is less than 2 parts by mass, it may not be possible to impart sufficient thermal conductivity to the composition. Also, if the amount of thermally conductive filler added exceeds 150 parts by mass, it may not be possible to disperse it in the low-melting-point metal, and it may end up in powder form.

[0020] Using two or more metal oxides and / or metal nitrides of component (B) with different average particle sizes is preferable because it improves the thermal conductivity of the composition. For example, as component (B), it is preferable that particles with an average particle diameter of 70 to 200 μm be present in an amount of 55% by mass or more and less than 100% by mass relative to the total amount of component (B), more preferably 57 to 90% by mass, and even more preferably 59 to 85% by mass.

[0021] The total content of component (A) and component (B) in the entire composition of the present invention is 95 to 100% by mass, preferably 98 to 100% by mass, and more preferably 99 to 100% by mass.

[0022] The following ingredients are optional and may be added as needed.

[0023] (C) Component Component (C) of the composition of the present invention is hydrophobic spherical silica fine particles, wherein the hydrophobic spherical silica fine particles consist of substantially SiO2 units obtained by hydrolysis and condensation of a tetrafunctional silane compound, a partially hydrolyzed condensation product thereof, or a mixture thereof, and have R on their surface. 1 SiO 3 / 2 Unit (R 1 (is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms), and R 2 3SiO 1 / 2 Unit (each R) 2These are monovalent hydrocarbon groups (which are identical or different, substituted or unsubstituted, with 1 to 6 carbon atoms) that have been introduced, with a particle size in the range of 0.005 to 1 μm and a particle size distribution D 90 / D 10 The value of is 3 or less, and the average circularity is between 0.8 and 1.

[0024] The hydrophobic spherical silica fine particles described above preferably have a particle size of 0.005 to 1 μm, more preferably 0.01 to 0.3 μm, and particularly preferably 0.03 to 0.25 μm. If the particle size is smaller than 0.005 μm, aggregation becomes severe, and if it is larger than 1 μm, the viscosity-reducing effect of the grease composition may be poor.

[0025] D is an indicator of the particle size distribution of the above hydrophobic spherical silica fine particles. 90 / D 10 The value of is preferably 3 or less, and more preferably 2.9 or less. Here, D 10 and D 90 These are values ​​obtained by measuring the particle size distribution. When measuring the particle size distribution of powder, D is the particle size that accounts for 10% of the cumulative total from the smallest particle size. 10 The particle size at which the cumulative total reaches 90% from the smallest side is D 90 That is what D 90 / D 10 Since the ratio is 3 or less, the particle size distribution of the hydrophobic spherical silica fine particles in the present invention is sharp. Having uniform particles with such a sharp particle size distribution is preferable because it is effective in reducing the viscosity of the grease composition.

[0026] In this invention, the particle size distribution of the fine particles was measured using a dynamic light scattering / laser Doppler nanotrack particle size distribution analyzer (manufactured by Nikkiso Co., Ltd., product name: UPA-EX150), and the volume-based median diameter was defined as the particle size. The median diameter is the particle size corresponding to 50% of the cumulative distribution when the particle size distribution is expressed as a cumulative distribution.

[0027] Furthermore, the average circularity of the above hydrophobic spherical silica nanoparticles is preferably 0.8 to 1. Here, "spherical" includes not only perfect spheres but also slightly distorted spheres. Such a "spherical" shape is evaluated by the circularity when the particle is projected in two dimensions, and refers to particles with a circularity in the range of 0.8 to 1. Here, circularity is (perimeter of a circle equal to the particle area) / (particle perimeter). The average circularity is the average value of the circularity measurements of 10 silica nanoparticles. This circularity can be measured by image analysis of particle images obtained with an electron microscope or the like.

[0028] In this specification, when hydrophilic spherical silica nanoparticles are described as "substantially consisting of SiO2 units," it means that the nanoparticles are basically composed of SiO2 units, but not solely of these units, and that they have a large number of silanol groups on their surface, as is commonly known. It also means that, in some cases, some of the hydrolyzable groups (hydrocarbyloxy groups) derived from the tetrafunctional silane compound used as a raw material and / or its partial hydrolysis condensation product may remain on or inside the nanoparticle surface without being converted to silanol groups.

[0029] In the composition of the present invention, when silica with small particle size obtained by hydrolysis of tetraalkoxysilane (sol-gel method) is used as the silica raw material (silica before hydrophobic treatment) and subjected to a specific surface treatment, a powder (hydrophobic spherical silica fine particles) is obtained, and since the particle size after hydrophobic treatment maintains the primary particle size of the silica raw material, aggregation of the hydrophobic spherical silica fine particles can be prevented.

[0030] To obtain silica raw materials of any desired particle size, the reaction conditions can be modified by using tetraalkoxysilane with a small number of carbon atoms in the alkoxy group as the silica raw material, using an alcohol with a small number of carbon atoms as the solvent, increasing the hydrolysis temperature, decreasing the concentration of tetraalkoxysilane during hydrolysis, and decreasing the concentration of the hydrolysis catalyst.

[0031] By applying a specific surface treatment to the silica raw material, desired hydrophobic spherical silica nanoparticles can be obtained. The following describes in detail the methods for producing hydrophobic spherical silica nanoparticles, but the methods for producing hydrophobic spherical silica nanoparticles are not limited to these.

[0032] <(C) Method for producing hydrophobic spherical silica fine particles> (C) The hydrophobic spherical silica nanoparticles of component (C) are Process (C1): Synthesis process for hydrophilic spherical silica nanoparticles. Process (C2): Surface treatment process with a trifunctional silane compound, Process (C3): Surface treatment process with monofunctional silane compound It is obtained by the following process. Each step will be explained in order below.

[0033] • Process (C1): Synthesis process for hydrophilic spherical silica nanoparticles General formula (I): Si(OR 3 )4(I) (In the formula, each R 3 (These are monovalent hydrocarbon groups with 1 to 6 carbon atoms, either identical or different.) A mixed solvent dispersion of hydrophilic spherical silica fine particles can be obtained by hydrolyzing and condensing a tetrafunctional silane compound represented by [formula], its partial hydrolysis product, or a mixture thereof in a mixture of a hydrophilic organic solvent containing a basic substance and water.

[0034] In general formula (I), R 3 R is a monovalent hydrocarbon group having 1 to 6 carbon atoms, preferably a monovalent hydrocarbon group having 1 to 4 carbon atoms, and particularly preferably a monovalent hydrocarbon group having 1 to 2 carbon atoms. 3 Examples of monovalent hydrocarbon groups represented by include alkyl groups such as methyl, ethyl, propyl, and butyl groups; and aryl groups such as phenyl groups. Preferably, methyl, ethyl, propyl, or butyl groups are used, and particularly preferably methyl or ethyl groups.

[0035] Examples of tetrafunctional silane compounds represented by general formula (I) include tetraalkoxysilanes such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane; and tetraphenoxysilane, preferably tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane, and particularly preferably tetramethoxysilane and tetraethoxysilane. Examples of partial hydrolysis condensation products of tetrafunctional silane compounds represented by general formula (I) include alkyl silicates such as methyl silicate and ethyl silicate.

[0036] The hydrophilic organic solvent is not particularly limited as long as it can dissolve the tetrafunctional silane compound represented by general formula (I), the partial hydrolysis condensation product thereof, and water. Examples include alcohols such as methanol, ethanol, propanol, isopropanol, and butanol; cellosolves such as methyl cellosolve, ethyl cellosolve, butyl cellosolve, and acetate cellosolve; ketones such as acetone and methyl ethyl ketone; and ethers such as dioxane and tetrahydrofuran. Preferably, alcohols and cellosolves are used, and alcohols are particularly preferred. Examples of alcohols include those represented by the following general formula (VII). R 11 OH (VII) (In the formula, R 11 (This refers to a monovalent hydrocarbon group with 1 to 6 carbon atoms.)

[0037] In general formula (VII), R 11 R is preferably a monovalent hydrocarbon group having 1 to 4 carbon atoms, and particularly preferably 1 to 2 carbon atoms. 11Examples of monovalent hydrocarbon groups represented by include alkyl groups such as methyl, ethyl, propyl, isopropyl, and butyl groups, preferably methyl, ethyl, propyl, and isopropyl groups, and more preferably methyl and ethyl groups. Examples of alcohols represented by general formula (VII) include methanol, ethanol, propanol, isopropanol, and butanol, with methanol and ethanol being preferred. Increasing the number of carbon atoms in the alcohol may increase the particle size of the resulting spherical silica fine particles. Therefore, methanol is preferred to obtain silica (silica raw material) with the desired small particle size.

[0038] Furthermore, examples of the basic substance include ammonia, dimethylamine, and diethylamine, preferably ammonia and diethylamine, and particularly preferably ammonia. These basic substances can be dissolved in the required amount in water, and the resulting aqueous solution (basic) can then be mixed with the hydrophilic organic solvent.

[0039] The amount of basic substance used is preferably 0.01 to 2 moles, more preferably 0.02 to 0.5 moles, and particularly preferably 0.04 to 0.12 moles, per mole of the total hydrocarbyloxy groups of the tetrafunctional silane compound represented by general formula (I) and / or its partial hydrolysis condensation product. In this case, the smaller the amount of basic substance, the smaller the desired particle size of silica (silica raw material) will be.

[0040] The amount of water used in the above hydrolysis and condensation is preferably 0.5 to 5 moles, more preferably 0.6 to 2 moles, and particularly preferably 0.7 to 1 mole, per mole of total hydrocarbyloxy groups of the tetrafunctional silane compound represented by general formula (I) and / or its partial hydrolysis condensation product. The ratio of the hydrophilic organic solvent to water (hydrophilic organic solvent:water) is preferably 0.5 to 10:1 by mass ratio, more preferably 3 to 9:1, and particularly preferably 5 to 8:1. The larger the amount of hydrophilic organic solvent, the smaller the desired particle size of silica (silica raw material) can be obtained.

[0041] The hydrolysis and condensation of tetrafunctional silane compounds represented by general formula (I) are carried out by well-known methods, namely by adding the tetrafunctional silane compound represented by general formula (I) to a mixture of a hydrophilic organic solvent containing a basic substance and water.

[0042] The concentration of hydrophilic spherical silica fine particles in the mixed solvent dispersion of the silica raw material (hydrophilic spherical silica fine particles) obtained in this step (C1) is generally 3 to 15% by mass, preferably 5 to 10% by mass.

[0043] • Process (C2): Surface treatment process with trifunctional silane compound In the mixed solvent dispersion of silica raw material (hydrophilic spherical silica fine particles) obtained in step (C1), the general formula (II): R 1 Si(OR 4 )3(II) (In the formula, R 1 R is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, each R 4 (These are monovalent hydrocarbon groups with 1 to 6 carbon atoms, either identical or different.) By adding a trifunctional silane compound represented by, its partial hydrolysis product, or a mixture thereof, and treating the surface of the hydrophilic spherical silica nanoparticles thereon, the surface of the hydrophilic spherical silica nanoparticles will be treated with R 1 SiO 3 / 2 Unit (R 1 A mixed solvent dispersion of first hydrophobic spherical silica fine particles is obtained by introducing a substituted or unsubstituted monovalent hydrocarbon group (having 1 to 20 carbon atoms).

[0044] This step (C2) is essential for suppressing the aggregation of silica microparticles in the subsequent concentration step. If the aggregation of silica microparticles is not suppressed, the resulting hydrophobic spherical silica microparticles will not be able to maintain their primary particle size, resulting in poor fluidity.

[0045] In general formula (II), R 1 This is preferably a monovalent hydrocarbon group having 1 to 3 carbon atoms, and particularly preferably 1 to 2 carbon atoms.1 Examples of monovalent hydrocarbon groups represented by include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, butyl, and hexyl groups, preferably methyl, ethyl, n-propyl, or isopropyl groups, and particularly preferably methyl or ethyl groups. Furthermore, some or all of the hydrogen atoms of these monovalent hydrocarbon groups may be substituted with halogen atoms such as fluorine, chlorine, or bromine atoms, preferably fluorine atoms.

[0046] In general formula (II), R 4 R is independently a monovalent hydrocarbon group, preferably having 1 to 3 carbon atoms, and particularly preferably 1 to 2 carbon atoms. 4 Examples of monovalent hydrocarbon groups represented by include alkyl groups such as methyl, ethyl, propyl, and butyl groups, preferably methyl, ethyl, or propyl groups, and particularly preferably methyl or ethyl groups.

[0047] Examples of trifunctional silane compounds represented by general formula (II) include unsubstituted or halogen-substituted trialkoxysilanes such as methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, isopropyltrimethoxysilane, isopropyltriethoxysilane, butyltrimethoxysilane, butyltriethoxysilane, hexyltrimethoxysilane, trifluoropropyltrimethoxysilane, and heptadecafluorodecyltrimethoxysilane. Preferably, these include methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, and ethyltriethoxysilane, more preferably methyltrimethoxysilane and methyltriethoxysilane, or their partial hydrolysis condensation products.

[0048] The amount of the trifunctional silane compound represented by general formula (II) added is 0.001 to 1 mole, preferably 0.01 to 0.1 moles, and particularly preferably 0.01 to 0.05 moles, per mole of Si atoms of the hydrophilic spherical silica fine particles used. If the amount added is less than 0.001 moles, the dispersibility of the resulting hydrophobic spherical silica fine particles will be poor, and the effect of imparting fluidity to boron nitride may not be obtained. If the amount added is more than 1 mole, aggregation of the silica fine particles may occur.

[0049] The concentration of the first hydrophobic spherical silica fine particles in the mixed solvent dispersion obtained in this step (C2) is 3% by mass or more and less than 15% by mass, preferably 5 to 10% by mass. If the concentration is less than 3% by mass, productivity may decrease, and if it is 15% by mass or more, aggregation of the silica fine particles may occur.

[0050] ·Concentration process A concentrated mixed solvent dispersion of the first hydrophobic spherical silica fine particles is obtained by removing a portion of the hydrophilic organic solvent and water from the mixed solvent dispersion of the first hydrophobic spherical silica fine particles obtained in this manner and concentrating the mixture. At this time, the hydrophobic organic solvent may be added in advance (before the concentration step) or during the concentration step. At this time, hydrocarbon-based or ketone-based solvents are preferred as the hydrophobic solvent used. Specifically, examples of hydrophobic solvents include toluene, xylene, methyl ethyl ketone, and methyl isobutyl ketone, with methyl isobutyl ketone being preferred. Methods for removing some of the hydrophilic organic solvent and water mentioned above include, for example, distillation and reduced-pressure distillation. The resulting concentrated mixed solvent dispersion preferably has a concentration of first hydrophobic spherical silica fine particles of 15 to 40% by mass, more preferably 20 to 35% by mass, and particularly preferably 25 to 30% by mass. If the concentration is less than 15% by mass, the surface treatment in step (C3) described later may not proceed smoothly, and if it is greater than 40% by mass, aggregation of silica fine particles may occur.

[0051] The concentration step also serves to suppress problems such as the silazane compound represented by general formula (III) and the monofunctional silane compound represented by general formula (IV), which are used as surface treatment agents in step (C3) described later, reacting with alcohol or water, resulting in insufficient surface treatment. This can lead to agglomeration during subsequent drying, causing the resulting silica powder to fail to maintain its primary particle size and resulting in poor fluidity.

[0052] • Process (C3): Surface treatment process with monofunctional silane compound To the concentrated mixed solvent dispersion obtained in the above concentration step, add the general formula (III): R 2 3SiNHSiR 2 3(III) (In the formula, each R 2 (These are monovalent hydrocarbon groups with 1 to 8 carbon atoms, either identical or different substituted or unsubstituted.) A silazane compound represented by, or general formula (IV): R 2 3SiX (IV) (In the formula, R 2 (where X is an identical or different substituted or unsubstituted monovalent hydrocarbon group having 1 to 6 carbon atoms, and X is an OH group or a hydrolyzable group.) The surface of the first hydrophobic spherical silica fine particles is treated by adding a monofunctional silane compound shown in or a mixture thereof, and the surface of the fine particles is treated with R 2 3SiO 1 / 2 Unit (R 2 By introducing (as defined in general formula (III)), a second hydrophobic spherical silica nanoparticle is obtained. Through this process, the silanol groups remaining on the surface of the first hydrophobic spherical silica nanoparticle are triorganosilylated in the form of R 2 3SiO 1 / 2 The unit is introduced to the surface.

[0053] In the above general formulas (III) and (IV), R 2 R is preferably a monovalent hydrocarbon group having 1 to 4 carbon atoms, and particularly preferably 1 to 2 carbon atoms. 2Examples of monovalent hydrocarbon groups represented by include alkyl groups such as methyl, ethyl, propyl, isopropyl, and butyl groups, preferably methyl, ethyl, or propyl groups, and particularly preferably methyl or ethyl groups. Furthermore, some or all of the hydrogen atoms of these monovalent hydrocarbon groups may be substituted with halogen atoms such as fluorine, chlorine, or bromine atoms, preferably fluorine atoms.

[0054] Examples of hydrolyzable groups represented by X include chlorine atoms, alkoxy groups, amino groups, and acyloxy groups, with alkoxy groups or amino groups being preferred, and alkoxy groups being particularly preferred.

[0055] Examples of silazane compounds represented by general formula (III) include hexamethyldisilazane, hexaethyldisilazane, and preferably hexamethyldisilazane. Examples of monofunctional silane compounds represented by general formula (IV) include monosilanol compounds such as trimethylsilanol and triethylsilanol; monochlorosilanes such as trimethylchlorosilane and triethylchlorosilane; monoalkoxysilanes such as trimethylmethoxysilane and trimethylethoxysilane; monoaminosilanes such as trimethylsilyldimethylamine and trimethylsilyldiethylamine; and monoacyloxysilanes such as trimethylacetoxysilane. Preferably, trimethylsilanol, trimethylmethoxysilane, or trimethylsilyldiethylamine are used, and particularly preferably, trimethylsilanol or trimethylmethoxysilane.

[0056] The amount of the silazane compound and / or monofunctional silane compound used is 0.1 to 0.5 moles, preferably 0.2 to 0.4 moles, and particularly preferably 0.25 to 0.35 moles, per mole of Si atoms of the hydrophilic spherical silica fine particles used. If the amount used is less than 0.1 moles, the dispersibility of the resulting hydrophobic spherical silica fine particles will be poor, and if the amount used is more than 0.5 moles, it will be economically disadvantageous.

[0057] The above hydrophobic spherical silica fine particles can be obtained as a powder by conventional methods such as atmospheric pressure drying or reduced pressure drying.

[0058] The amount of component (C) is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, and particularly preferably 0.1 to 5 parts by mass, per 100 parts by mass of component (A). If the amount is less than 0.01 parts by mass, the effect of adding component (C), such as the effect of lowering the viscosity of the grease composition, will not be obtained, and if it exceeds 10 parts by mass, the viscosity of the grease composition will increase, which may worsen the thermal conductivity and is also uneconomical.

[0059] (D) Component Component (D) is added to the composition for the purpose of treating the surface of the powder (components (B) and / or (C)), not only to help with high powder packing but also to improve the moisture resistance of component (A). Originally, gallium and gallium alloys themselves had the drawback that oxidation progressed when exposed to high humidity for a long time, resulting in an increase in the thermal resistance of the silicone composition. However, by including component (D), no increase in thermal resistance is observed even under high humidity, and the performance can be maintained. Component (D) is an organosilane represented by the following general formula (1). R 1 a R 2 b Si(OR 3 ) 4-a-b (1) (In the formula, R 1 Each of these is independently a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, and R 2 Each of these is independently a substituted or unsubstituted monovalent hydrocarbon group other than an alkyl group, and R 3 (where a is a monovalent hydrocarbon group with 1 to 6 carbon atoms, either identical or different, a is a number from 1 to 3, b is a number from 0 to 2, and the sum of a + b is a number from 1 to 3.)

[0060] R in equation (1) above 1Examples include methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, nonyl, decyl, dodecyl, tetradecyl, hexadecyl, octadecyl, and eicosyl groups; cycloalkyl groups such as cyclopentyl and cyclohexyl groups; and halogen-substituted alkyl groups such as 3-chloropropyl, 3,3,3-trifluoropropyl, 2-(nonafluorobutyl)ethyl, and 2-(heptadecafluorooctyl)ethyl groups. If the number of carbon atoms exceeds 20, the organosilane solidifies at room temperature, making it inconvenient to handle and reducing the low-temperature properties of the resulting composition. When a in formula (1) is 2 or 3, R 1 These may be the same type of group or different types of groups. Also, R in equation (1) above 2 Examples of such groups include alkenyl groups such as vinyl and allyl groups; aryl groups such as phenyl and tolyl groups; aralkyl groups such as 2-phenylethyl and 2-methyl-2-phenylethyl groups; and halogenated hydrocarbon groups such as p-chlorophenyl groups. Among these, methyl and ethyl groups are particularly preferred. Also, R in equation (1) above 3 Examples of alkyl groups include methyl, ethyl, propyl, butyl, pentyl, and hexyl groups. Among these, methyl and ethyl groups are particularly preferred.

[0061] The following are some suitable examples of this component (D). CH3Si(OCH3)3 C3H7Si(OCH3)3 C6H 13 Si(OCH3)3 C8H 17 Si(OCH3)3 C 10 H 21 Si(OCH3)3 C 12 H 25 Si(OCH3)3 C 16 H 33 Si(OCH3)3 C 18 H37 Si(OCH3)3 C 20 H 41 Si(OCH3)3 C3H7Si(OC2H5)3 C6H 13 Si(OC2H5)3 C8H 17 Si(OC2H5)3 C 10 H 21 Si(OC2H5)3 C 12 H 25 Si(OC2H5)3 C 18 H 37 Si(OC2H5)3 C 10 H 21 Si(CH3)(OCH3)2 C 10 H 21 Si(C6H5)(OCH3)2 C 10 H 21 Si(CH3)(OC2H5)2 C 10 H 21 Si(CH=CH2)(OCH3)2 C 10 H 21 Si(CH2CH2CF3)(OCH3)2 (ClCH2CH2CH2)Si(OCH3)3 (ClCH2CH2CH2)Si(OC2H5)3 Incidentally, this component (D) may be used singly or in combination of two or more kinds.

[0062] The blending amount of component (D) is preferably 0.001 to 10 parts by mass, more preferably 0.001 to 5 parts by mass, and particularly preferably 0.001 to 2.5 parts by mass, relative to 100 parts by mass of component (A). If the blending amount exceeds 10 parts by mass, the moisture resistance improving effect will not increase, which is uneconomical, and since it has slight volatility, the composition of the present invention may gradually harden if left to stand in an open system.

[0063] Other Components Furthermore, the thermally conductive composition of the present invention may optionally contain conventionally known antioxidants, dyes, pigments, flame retardants, settling inhibitors, and thixotropic enhancers, to the extent that they do not impair the objectives of the present invention.

[0064] Manufacturing of the composition The method for producing the thermally conductive composition of the present invention may follow conventionally known methods for producing silicone grease compositions and is not particularly limited. However, while conventionally known methods use silicone oil as a base, the present production method uses a low-melting-point metal as a base to which each component is added. As a specific production method, for example, the above components (A) and (B), and optionally components (C), (D), and / or other components, can be mixed for 30 minutes to 4 hours in a mixer in which the stirring blades move in a planetary motion (rotation and revolution) in a stirring tank, such as Trimix, Twinmix, Planetary Mixer (all mixers manufactured by Inoue Seisakusho Co., Ltd., registered trademarks), Ultra Mixer (a mixer manufactured by Mizuho Industries, Ltd., registered trademark), Hibis Disper Mix (a mixer manufactured by Tokushu Kika Kogyo Co., Ltd., registered trademark), etc. If component (A) is solid at room temperature, it is preferable to heat it beforehand to dissolve it before blending. Alternatively, if necessary, it may be mixed while heating at a temperature in the range of 50 to 150°C. Furthermore, each component may be mixed all at once, or it may be mixed in stages.

[0065] [Thermal conductivity] The thermal conductivity of the thermally conductive composition of the present invention is preferably 30.0 W / m·K or higher at 25°C, more preferably 35.0 W / m·K or higher, and even more preferably 40.0 W / m·K or higher. By using materials with high thermal conductivity for both the low-melting-point metal base material and the filler, the thermally conductive composition of the present invention can achieve an even higher thermal conductivity.

[0066] The thermally conductive composition of the present invention can be used as a grease. The manner in which the composition of the present invention is used as a grease is not particularly limited, and it can be used in the same manner as conventional heat-dissipating (thermally conductive) silicone greases. For example, it can be suitably used in a manner in which the grease is sandwiched between electrical and electronic components such as LSIs or other heat-generating elements and a cooling or heat-dissipating element, thereby transferring heat from the heat-generating element to the cooling or heat-dissipating element for heat dissipation. Because the thermally conductive composition of the present invention has high thermal conductivity and excellent workability, it can be suitably used as a heat-dissipating (thermally conductive) grease for high-grade semiconductor devices and the like. [Examples]

[0067] The present invention will be specifically described below using examples and comparative examples, but the present invention is not limited to these.

[0068] (A) component (A-1) Metallic gallium [Melting point = 29.8°C] (A-2) Ga-In alloy [mass ratio = 75.4:24.6, melting point = 15.7℃] (A-3) Ga-In-Sn alloy [mass ratio = 68.5:21.5:13, melting point = -19℃] (A-4) Ga-In-Sn alloy [mass ratio = 62:25:13, melting point = 5.0℃] (A-5) Ga-In-Zn alloy [mass ratio = 82:12:6, melting point = 17℃]

[0069] (B) Component (B-1) Aluminum nitride powder [Average particle size: 100 μm] (B-2) Aluminum nitride powder [Average particle size: 70 μm] (B-3) Aluminum nitride powder [Average particle size: 60 μm] (B-4) Aluminum nitride powder [Average particle size: 20 μm] (B-5) Aluminum nitride powder [Average particle size: 5 μm] (B-6) Aluminum nitride powder [Average particle size: 1 μm] (B-7) Zinc oxide powder [Average particle size: 1 μm]

[0070] Particle size measurement The particle size of the thermally conductive filler (component (B)) was measured using a laser diffraction / scattering particle size distribution analyzer (in this example, a Microtrac MT3300EX particle size analyzer manufactured by Nikkiso Co., Ltd.). The measured particle size is the cumulative average diameter based on volume.

[0071] (C) Components: Hydrophobic spherical silica microparticles Component (C) was prepared as hydrophobic spherical silica fine particles (C-1) to (C-6) as follows (Table 1). Of these, (C-5) and (C-6) are for comparative examples.

[0072] (D) Component (D-1) Structural formula: C 10 H 21 Organosilanes represented by Si(OCH3)3 (D-2) Structural formula: C 16 H 33 Organosilanes represented by Si(OCH3)3 (D-3) Organosilane represented by the structural formula: (ClCH2CH2CH2)Si(OCH3)3

[0073] [Synthesis of hydrophobic spherical silica nanoparticles] [Synthesis Example 1] • Process (C1): Synthesis process for hydrophilic spherical silica nanoparticles In a 3-liter glass reactor equipped with a stirrer, a dropping funnel, and a thermometer, 989.5 g of methanol, 135.5 g of water, and 66.5 g of 28% by mass aqueous ammonia were mixed. The temperature of this solution was adjusted to 35°C, and 436.5 g (2.87 mol) of tetramethoxysilane was added dropwise over 6 hours while stirring. After the addition was complete, stirring was continued for another 0.5 hours to carry out hydrolysis, thereby obtaining a suspension of hydrophilic spherical silica nanoparticles.

[0074] • Process (C2): Surface treatment process with trifunctional silane compound To the suspension obtained in step (C1), 4.4 g (0.03 mol) of methyltrimethoxysilane was added dropwise over 0.5 hours at room temperature. Stirring was continued for 12 hours after the addition of the silica nanoparticles to hydrophobicize the surface of the silica nanoparticles, thereby obtaining a dispersion of hydrophobic spherical silica nanoparticles. ·Concentration process Next, an ester adapter and a condenser were attached to a glass reactor, and the dispersion obtained in step (C2) was heated to 60-70°C to remove 1,021 g of methanol and water mixture, thereby obtaining a concentrated dispersion of hydrophobic spherical silica fine particles in a mixed solvent. At this time, the content of hydrophobic spherical silica fine particles in the concentrated dispersion was 28% by mass.

[0075] • Process (C3): Surface treatment process with monofunctional silane compound To the concentrated dispersion obtained in the concentration step, 138.4 g (0.86 mol) of hexamethyldisilazane was added at room temperature. The dispersion was then heated to 50-60°C and reacted for 9 hours to trimethylsilylate the silica nanoparticles in the dispersion. Next, the solvent in the dispersion was removed by distillation at 130°C under reduced pressure (6,650 Pa) to obtain 186 g of hydrophobic spherical silica nanoparticles (C-1).

[0076] The hydrophilic spherical silica nanoparticles obtained in step (C1) were measured according to measurement method 1 below. Furthermore, the hydrophobic spherical silica nanoparticles obtained through each of the above steps (C1) to (C3) were measured according to measurement methods 2 and 3 below. The results are shown in Table 1.

[0077] [Measurement method 1~3] 1. Measurement of particle size of hydrophilic spherical silica fine particles obtained in step (C1) A silica microparticle suspension was added to methanol to a concentration of 0.5% by mass, and the microparticles were dispersed by ultrasonic testing for 10 minutes. The particle size distribution of the treated microparticles was measured using a dynamic light scattering / laser Doppler nanotrack particle size distribution analyzer (manufactured by Nikkiso Co., Ltd., product name: UPA-EX150), and the volume-based median diameter was defined as the particle size. The median diameter is the particle size corresponding to 50% of the cumulative distribution when the particle size distribution is expressed as a cumulative distribution.

[0078] 2. Particle size measurement and particle size distribution D of hydrophobic spherical silica fine particles obtained in step (C3) 90 / D 10 Measurement Silica microparticles were added to methanol to a concentration of 0.5% by mass, and the particles were dispersed by ultrasonic treatment for 10 minutes. The particle size distribution of the treated microparticles was measured using a dynamic light scattering / laser Doppler nanotrack particle size distribution analyzer (manufactured by Nikkiso Co., Ltd., product name: UPA-EX150), and the volume-based median diameter was defined as the particle size. Particle size distribution D 90 / D 10 The measurement is performed by determining the particle size at which the cumulative total from the smallest particle size in the distribution measured above reaches 10%. 10 The particle size at which the cumulative total reaches 90% is D. 90 Based on the measured values, D 90 / D 10 I calculated it.

[0079] 3. Measurement of the shape and circularity of hydrophobic spherical silica particles The shape was confirmed by observation using an electron microscope (Hitachi, Ltd., product name: S-4700, magnification: 100,000x). "Spherical" includes not only perfect spheres but also slightly distorted spheres. The shape of these particles was evaluated by their circularity when projected onto a two-dimensional surface. Here, circularity is defined as (perimeter of a circle equal to the particle area) / (particle perimeter), and was considered to be in the range of 0.8 to 1. The circularity was the average value obtained from measuring 10 particles.

[0080] [Synthesis Example 2] In Synthesis Example 1, the process was carried out in the same manner as in Synthesis Example 1, except that the amounts of methanol, water, and 28% by mass aqueous ammonia were changed in step (C1) to 1,045.7 g of methanol, 112.6 g of water, and 33.2 g of 28% by mass aqueous ammonia. 188 g of hydrophobic spherical silica nanoparticles (C-2) were obtained. Measurements were performed using these hydrophobic spherical silica nanoparticles (C-2) in the same manner as in Synthesis Example 1. The results are shown in Table 1.

[0081] [Synthesis Example 3] ·Process (C1): In a 3-liter glass reactor equipped with a stirrer, dropping funnel, and thermometer, 623.7 g of methanol, 41.4 g of water, and 49.8 g of 28% by mass aqueous ammonia were added and mixed. This solution was adjusted to 35°C, and while stirring, 1,163.7 g of tetramethoxysilane and 418.1 g of 5.4% by mass aqueous ammonia were simultaneously added to the solution, the former over 6 hours and the latter over 4 hours. Stirring was continued for 0.5 hours after the addition of tetramethoxysilane to carry out hydrolysis and obtain a suspension of silica nanoparticles. ·Process (C2): To the resulting suspension, 11.6 g of methyltrimethoxysilane (equivalent to 0.01 molar ratios to tetramethoxysilane) was added dropwise at room temperature over 0.5 hours, and the mixture was stirred for another 12 hours after the addition to treat the surface of the silica nanoparticles. An ester adapter and a condenser were attached to the glass reactor, and 1,440 g of methyl isobutyl ketone was added to a dispersion containing silica fine particles that had undergone the above surface treatment. The mixture was then heated to 80-110°C, and methanol water was removed by distillation over 7 hours. ·Process (C3): To the resulting dispersion, 357.6 g of hexamethyldisilazane was added at room temperature, and the mixture was heated to 120°C and reacted for 3 hours to trimethylsilylate the silica nanoparticles. The solvent was then removed under reduced pressure to obtain 472 g of hydrophobic spherical silica nanoparticles (C-3). The hydrophobic spherical silica nanoparticles (C-3) obtained in this manner were measured in the same manner as in Synthesis Example 1. The results are shown in Table 1.

[0082] [Synthesis Example 4] In the synthesis of silica nanoparticles, each step was carried out in the same manner as in Synthesis Example 3, except that the hydrolysis temperature of tetramethoxysilane was changed from 35°C to 20°C. This yielded 469 g of hydrophobic spherical silica nanoparticles (C-4). Measurements were performed using these hydrophobic spherical silica nanoparticles (C-4) in the same manner as in Synthesis Example 1. The results are shown in Table 1.

[0083] [Comparative Synthesis Example 1] 100 g of silica (product name: SOC1, manufactured by Admatex Co., Ltd.), produced by deflagration, was charged into a 0.3 liter glass reactor equipped with a stirrer and thermometer. 1 g of pure water was added under stirring, and after sealing, the reactor was stirred at 60°C for 10 hours. Next, after cooling to room temperature, 2 g of hexamethyldisilazane was added under stirring, and after sealing, the reactor was stirred for a further 24 hours. The temperature was raised to 120°C, and residual raw materials and generated ammonia were removed while passing nitrogen gas through the reactor to obtain 100 g of hydrophobic spherical silica fine particles (C-5). The obtained hydrophobic spherical silica nanoparticles (C-5) were measured in the same manner as in Synthesis Example 1. The results are shown in Table 1.

[0084] [Comparative Synthesis Example 2] 100 g of silica (product name: SOC1, manufactured by Admatex Co., Ltd.) produced by deflagration was charged into a 0.3 liter glass reactor equipped with a stirrer and thermometer. 1 g of pure water was added under stirring, and after sealing, the reactor was stirred at 60°C for 10 hours. Next, after cooling to room temperature, 1 g of methyltrimethoxysilane was added under stirring, and after sealing, the reactor was stirred for a further 24 hours. Then, 2 g of hexamethyldisilazane was added under stirring, and after sealing, the reactor was stirred for a further 24 hours. The temperature was raised to 120°C, and residual raw materials and generated ammonia were removed while passing nitrogen gas through the reactor to obtain 101 g of hydrophobic spherical silica nanoparticles (C-6). The obtained hydrophobic spherical silica nanoparticles (C-6) were measured in the same manner as in Synthesis Example 1. The results are shown in Table 1.

[0085] [Table 1] <Note> 1) Particle size of hydrophilic spherical silica fine particles of the dispersion obtained in step (C1) 2) Particle size of the hydrophobic spherical silica fine particles obtained in the final product

[0086] [Examples 1-31, Comparative Examples 1-2] <Preparation of Composition> Each component was sampled in the compositional ratios listed in Tables 2-6, placed in a 1-liter planetary mixer (for example, a PRIMIX product, product name: Hibiscus Mix 2P-1), and stirred at room temperature for 1 hour to prepare each composition. For (A-1), which has a melting point higher than room temperature, the product was melted in the oven beforehand and then added.

[0087] <Exterior> The properties of each obtained composition were visually inspected. The results are shown in Tables 2-6.

[0088] <Measurement of thermal conductivity> The thermal conductivity of each composition was measured at 25°C using a thermophysical property measuring device that utilizes the hot disk method (in this example, a TPS-2500S manufactured by Kyoto Electronics Manufacturing Co., Ltd.).

[0089] <Assessment of workability> Each composition was filled into a disposable syringe (e.g., Terumo Syringe SS-02SZ 2.5 mL, medium-sized, without needle) with approximately 1.5 mL of the composition, and then the plunger was pressed to dispense it. When the dispensed composition was spread out with a spatula or similar tool, if it spread out evenly, it was judged to have good workability ("○" - it was difficult to return to a droplet after being crushed) (Figure 1). If it did not spread out sufficiently, it was judged to have poor workability ("×" - it was easy to return to a droplet after being crushed) (Figure 2).

[0090] [Table 2]

[0091] [Table 3]

[0092] [Table 4]

[0093] [Table 5]

[0094] [Table 6]

[0095] From the examples, it was found that the thermally conductive composition of the present invention has excellent workability and high thermal conductivity. In particular, from Examples 21 to 29, it was found that the thermal conductivity is improved when metal oxides and / or metal nitrides with an average particle size of 70 to 200 μm are added as component (B) in a high proportion of 55% to less than 100% by mass relative to the total amount of component (B). Examples 21-29 show that a preferred formulation with high thermal conductivity and excellent workability is: • Component (B) with an average particle size of 70-200 μm: 55% by mass or more of component (B) • Component (B) with an average particle size of 20 μm or more and less than 70 μm: 10-35% by mass of component (B) • Component (B) with an average particle size of less than 20 μm: 30% by mass or less of component (B) The composition includes, and a more preferred formulation is, • Component (B) with an average particle size of 70-200 μm: 57% by mass or more of component (B): • Component (B) with an average particle size of 20 μm or more and less than 70 μm: 12-30% by mass • Component (B) with an average particle size of less than 20 μm: 28% by mass or less The composition includes, and a more preferred example of a formulation is: • Component (B) with an average particle size of 70-200 μm: 59% by mass or more of component (B): • Component (B) with an average particle size of 20 μm or more and less than 70 μm: 14-28% by mass • Component (B) with an average particle size of less than 20 μm: 26% by mass or less It was found to be a component of the composition.

Claims

1. (A) Gallium and / or its alloys having a melting point of -20 to 100°C: 100 parts by mass, (B) Metal oxides and / or metal nitrides having an average particle size of 0.01 μm to 200 μm: 2 to 150 parts by mass per 100 parts by mass of component (A) A thermally conductive composition comprising the above-mentioned (A) and (B), wherein the total content of the above-mentioned (A) and (B) in the composition is 95 to 100% by mass, and the base oil content in the composition is 0.5% by mass or less.

2. The thermally conductive composition according to claim 1, wherein the total content of component (A) and component (B) in the composition is 98 to 100% by mass.

3. The thermally conductive composition according to claim 1, wherein the gallium alloy of component (A) is one or more selected from Ga-In alloy, Ga-Sn-Zn alloy, Ga-In-Sn alloy, and Ga-In-Bi-Sn alloy.

4. The thermally conductive composition according to claim 1, wherein component (B) is one or more selected from zinc oxide powder, alumina powder, boron nitride powder, silicon nitride powder, aluminum nitride powder, aluminum hydroxide powder, and magnesium oxide powder.

5. Furthermore, the thermally conductive composition according to claim 1, further comprising 0.01 to 10 parts by mass of the following hydrophobic spherical silica fine particles as component (C) per 100 parts by mass of component (A). Substantially SiO obtained by hydrolyzing and condensing a tetrafunctional silane compound, a partial hydrolysis-condensation product thereof, or a mixture of these 2 On the surface of hydrophilic spherical silica fine particles composed of units, R 1 SiO 3 / 2 unit (R 1 is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms) is introduced, and R 2 3 SiO 1 / 2 unit (each R 2 are identical or different, and each is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 8 carbon atoms) is introduced, the particle diameter is in the range of 0.005 to 1 μm, the particle size distribution D 90 / D 10 has a value of 3 or less, and an average circularity of 0.8 to 1, the hydrophobic spherical silica fine particles.

6. Furthermore, the thermally conductive composition according to claim 1, wherein the (D) component contains 0.001 to 10 parts by mass of an organosilane represented by the following general formula (1) per 100 parts by mass of component (A). R 1 a R 2 b Si(OR 3 ) 4-a-b (1) (In the formula, R 1 Each is independently a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, and R 2 Each of these is independently a substituted or unsubstituted monovalent hydrocarbon group other than an alkyl group, and R 3 (where a is a monovalent hydrocarbon group with 1 to 6 carbon atoms, either identical or different, a is a number from 1 to 3, b is a number from 0 to 2, and the sum of a + b is a number from 1 to 3.)

Citation Information

Patent Citations

  • Liquid metal matrix thermal paste and its manufacture

    JP1991071992A

  • Manufacturing method of thermal conductive compound by crosslinking particle cluster of liquid metal

    JP2001329068A

  • Thermally conductive silicone composition, cured product thereof and method for laying the same, and heat- releasing structure for semiconductor device using the same

    JP2003176414A

  • Heat radiating member and method for manufacturing and for installing the same

    JP2003218296A

  • Heat radiation member, its manufacturing method, and its lay-out method

    JP2004039829A